The effect of Budget Announcement on Sri Lankan Stock Prices. - Koperunthevy, K. (Gokaraju Rangaraju Institude of Engineering and Technology, Hyderabad., 2018)
The stock prices of a stock market reflect all pertinent information available to investors and other participants. If a stock market is efficient, the stock prices will reflect according to the available information of economic, political and social events. So, in an efficient market stock prices reflect all available information. Therefore, the aim of the study is to find out the effect of budget announcement on Sri Lankan stock prices. The study examines the behavior of Sri Lankan stock price indices in respect of pre and post period of budget announcement. The data were collected from Colombo Stock Exchange (CSE) database. The collected data includes All Share Price Index (ASPI) and for 20 sectors’ stock price indices to examine the pre and post budget announcement effect in the year 2017. The event study method was adopted to examine the market efficiency and pre and post period of 15 day-event window was considered on the first budget speech date at parliament. The Average Abnormal Return (AAR), the Cumulative Abnormal Return (CAAR) and t-statistic were used to test the market efficiency to budget announcement. CAARs are statistically significant from-1 day to +15 day expect + 5 day. Further, a negative downward trend is observed on the stock price indices. Therefore, the study concludes that stock market efficiency level is high and investors cannot an abnormal return in the stock exchange without taking additional risk.
Keywords: Budget announcement.; AAR.; CAAR.; All share price index; CSE.